1993
DOI: 10.1530/jrf.0.0980097
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotrophin-releasing hormone and the control of ovulation rate by the FecB gene in Booroola ewes

Abstract: Booroola sheep carry a FecB gene that confers high fecundity. The aims of the present studies were to determine in homozygous carriers (BB) and non-carriers (++) of the Booroola FecB gene whether there are FecB differences in the secretory characteristics of GnRH in hypophyseal-portal blood of ovariectomized ewes (Expt 1) and whether differences in ovulation rate would occur following the administration of PMSG and pulsatile GnRH to ovary-intact Booroola ewes with hypothalamic-pituitary disconnection (HPD) (Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 20 publications
2
17
0
Order By: Relevance
“…Earlier studies failed to produce convincing evidence that differences in circulating concentrations of gonadotropic hormones were solely responsible for differences in ovulation rate in ewes [34]. It has been suggested that the high ovulation rate in prolific sheep is due to intraovarian rather than pituitary factors [34][35][36]. We propose that the difference in the pattern of follicle development and ovulation rate between breeds of sheep differing in prolificacy may be partly due to a difference in circulating concentrations of progesterone.…”
Section: Discussionmentioning
confidence: 81%
“…Earlier studies failed to produce convincing evidence that differences in circulating concentrations of gonadotropic hormones were solely responsible for differences in ovulation rate in ewes [34]. It has been suggested that the high ovulation rate in prolific sheep is due to intraovarian rather than pituitary factors [34][35][36]. We propose that the difference in the pattern of follicle development and ovulation rate between breeds of sheep differing in prolificacy may be partly due to a difference in circulating concentrations of progesterone.…”
Section: Discussionmentioning
confidence: 81%
“…The plasma concentrations of FSH were found to be consistently higher in the homozygous Booroola ewes compared with the wild-type (WT) ewes throughout the oestrous cycle, anoestrus and after ovariectomy. They were also found to be higher in ovariectomised or ovary-intact ewes treated with gonadotrophin-releasing hormone (GnRH) following hypothalamic-pituitary disconnection (HPD; McNatty et al 1987McNatty et al , 1989McNatty et al , 1991aMcNatty et al , 1993. When HPD or Deslorelin-treated (GnRH agonist) homozygous ALK6 (BB) and WTewes were administered identical doses of FSH, the ovulation rate and plasma concentrations of FSH in those animals which ovulated was the same in both genotypes (Hudson et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In ram lambs, the effects of the FecBB gene on plasma hormone concentrations are equivocal (Seek el al, 1988;Montgomery et al, 1989;Purvis el al, 1991) and, to our (Bindon, 1984;McNatty et al, 1991aMcNatty et al, , 1992Montgomery el al, 1992 (McNatty et al, 1987a(McNatty et al, , 1989(McNatty et al, , 1993a. In rams, most studies have found no effect of the FecBB gene on plasma FSH and LH concentrations that are independent of sire effects (Bindon et al, 1985(Bindon et al, , 1989Montgomery et al, 1989;Hochereau-de Reviers and Seek, 1991;Price et al, 1991a, b, c;Isaacs et al, 1992 (1982).…”
Section: Introductionmentioning
confidence: 99%